Foliar Herbivory Reduces Rhizosphere Fungal Diversity and Destabilizes the Co-occurrence Network - Shi, Yu; Zhang, Kaoping; Ma, Tiantian; Zhang, Zhongyue; Li, Ping; Xing, Zhenlong; Ding, Jianqing (Frontiers in Microbiology, 2022)
Insect herbivores can adversely impact terrestrial plants throughout ontogeny and across various ecosystems. Simultaneously, the effects of foliar herbivory may extend belowground, to the soil microbial community. However, the responses in terms of the diversity, assembly and stability of rhizosphere fungi to aboveground herbivory remain understudied. Here, using high-throughput sequencing, the effects of foliar insect herbivory on rhizosphere fungal microbes were investigated in a common garden experiment that manipulated herbivory intensity and time from herbivore removal. The number of observed fungal species was reduced by a greater herbivory intensity, with some species evidently sensitive to herbivory intensity and time since herbivore removal. Rhizofungal assembly processes were altered by both herbivory intensity and time since herbivore removal. Further, we found evidence that both factors strongly influenced fungal community stability: a high intensity of herbivory coupled with a shorter time since herbivore removal resulted in low stability. These results suggest that foliar herbivory can adversely alter fungal diversity and stability, which would in turn be harmful for plant health. Fortunately, the effect seems to gradually diminish with time elapsed after herbivore removal. Our findings provide a fresh, in-depth view into the roles of rhizofungi in enhancing the adaption ability of plants under environmental stress.